Partial Protection against Porcine Influenza A Virus by a Hemagglutinin-Expressing Virus Replicon Particle Vaccine in the Absence of Neutralizing Antibodies - Ricklin, Meret E.; Vielle, Nathalie J.; Python, Sylvie; Brechbühl, Daniel; Zumkehr, Beatrice; Posthaus, Horst; Zimmer, Gert; Summerfield, Artur (Frontiers in Immunology, 2016)
This work was initiated by previous reports demonstrating that mismatched influenza A virus (IAV) vaccines can induce enhanced disease, probably mediated by antibodies. Our aim was therefore to investigate if a vaccine inducing opsonizing but not neutralizing antibodies against the hemagglutinin (HA) of a selected heterologous challenge virus would enhance disease or induce protective immune responses in the pig model. To this end, we immunized pigs with either whole inactivated virus (WIV)-vaccine or HA-expressing virus replicon particles (VRP) vaccine based on recombinant vesicular stomatitis virus. Both types of vaccines induced virus neutralizing and opsonizing antibodies against homologous virus as shown by a highly sensitive plasmacytoid dendritic cell-based opsonization assay. Opsonizing antibodies showed a broader reactivity against heterologous IAV compared to neutralizing antibodies. Pigs immunized with HA-recombinant VRP vaccine were partially protected from infection with a mismatched IAV, which was not neutralized but opsonized by the immune sera. The VRP vaccine reduced lung lesions, lung inflammatory cytokine responses, serum IFN-α responses and viral loads in the airways. Only the VRP vaccine was able to prime IAV-specific IFNγ/TNFα dual secreting CD4+ T cells detectable in the peripheral blood. In summary, this work demonstrates that with the virus pair selected, a WIV vaccine inducing opsonizing antibodies against HA which lack neutralizing activity, is neither protective nor does it induce enhanced disease in pigs. In contrast, VRP expressing HA are efficacious vaccines in swine as they induced both, potent antibodies and T-cell immunity resulting in a broader protective value.